Ezetimibe ameliorates clinical symptoms in a mouse model of ankylosing spondylitis associated with suppression of Th17 differentiation - Moon, Jeonghyeon; Lee, Seon-Yeong; Na, Hyun Sik; Lee, A Ram; Cho, Keun-Hyung; Choi, Jeong Won; Park, Sung-Hwan; Cho, Mi-La (Frontiers in Immunology, 2022)
Ankylosing spondylitis (AS) is a chronic inflammatory disease that causes spinal inflammation and fusion. Although the cause of AS is unknown, genetic factors (e.g., HLA-B27) and environmental factors (e.g., sex, age, and infection) increase the risk of AS. Current treatments for AS are to improve symptoms and suppress disease progression. There is no way to completely cure it. High blood cholesterol and lipid levels aggravate the symptoms of autoimmune diseases. We applied hyperlipidemia drugs ezetimibe and rosuvastatin to AS mice and to PBMCs from AS patients. Ezetimibe and rosuvastatin was administered for 11 weeks to AS model mice on the SKG background. Then, the tissues and cells of mice were performed using flow cytometry, computed tomography, immunohistochemistry, and immunofluorescence. Also, the normal mouse splenocytes were cultured in Th17 differentiation conditions for in vitro analysis such as flow cytometry, ELISA and RNA sequencing. The 10 AS patients’ PBMCs were treated with ezetimibe and rosuvastatin. The patients’ PBMC were analyzed by flow cytometry and ELISA for investigation of immune cell type modification. Ezetimibe caused substantial inhibition for AS. The present study showed that ezetimibe inhibits Th17 cell function, thereby slowing the progression of AS. It is well known that statins are more effective in reducing blood lipid concentrations than ezetimibe, however, our results that ezetimibe had a better anti-inflammatory effect than rosuvastatin in AS. This data suggests that ezetimibe has an independent anti-inflammatory effect independent of blood lipid reduction. To investigate whether ezetimibe has its anti-inflammatory effect through which signaling pathway, various in vitro experiments and RNA sequencing have proceeded. Here, this study suggests that ezetimibe can be an effective treatment for AS patients by inhibiting Th17 differentiation-related genes such as IL-23R and IL-1R. Thus, this study suggests that ezetimibe has therapeutic potential for AS through inhibition of Th17 differentiation and the production of pro-inflammatory cytokines.